Pengaruh Penempatan Kerja dan Pelatihan Kerja Terhadap Prestasi Kerja Karyawan PT Firisian Flag - Purba, Rahel; Andara, Adissya Maya (Jurnal ATAMA, 2023)
The purpose of this study was to determine the effect of job placement and job training on employee performance. The population in this study were employees of PT Frisian Flag, totaling 50 employees, the sample and this study were the employees. The analytical technique used in this research is quantitative method. Data collection techniques used in this study were observation, questionnaires. Data were collected and processed using SPSS computing program. The results of this study have a positive and significant effect on employee performance and show a correlation between placement and job training on job performance which has a strong influence. The results showed that partially the work placement variable had a positive effect on work performance, and job training has a positive effect on work performance. And simultaneously the variable of job placement and job training has a positive effect on work performance.